2021
DOI: 10.3390/ani11051211
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Characterization of Vomeronasal Organ Aging in Mice

Abstract: The vomeronasal organ (VNO) plays a crucial role in animal behavior since it is responsible for semiochemical detection and, thus, for intra- and interspecific chemical communication, through the vomeronasal sensory epithelium (VNSE), composed of bipolar sensory neurons. This study aimed to explore a well-recognized cause of neuronal degeneration, only rarely explored in this organ: aging. Murine VNOs were evaluated according to 3 age groups (3, 10, and 24 months) by histology to assess VNSE changes such as ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…1 ). Our findings are consistent with two previous studies (Brann and Firestein, 2010, Mechin et al, 2021), which reported an overall thinning of the vomeronasal sensory epithelium (Mechin et al, 2021) and reduced VSE neurogenesis in the marginal zone of 2-year-old animals (Brann and Firestein, 2010). Here, we expand the current knowledge with novel information from a commonly used AD animal model (APP/PS1 Het ), revealing an unexpected preservation of the VSE proliferative capabilities in middle age APP/PS1 Het mice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1 ). Our findings are consistent with two previous studies (Brann and Firestein, 2010, Mechin et al, 2021), which reported an overall thinning of the vomeronasal sensory epithelium (Mechin et al, 2021) and reduced VSE neurogenesis in the marginal zone of 2-year-old animals (Brann and Firestein, 2010). Here, we expand the current knowledge with novel information from a commonly used AD animal model (APP/PS1 Het ), revealing an unexpected preservation of the VSE proliferative capabilities in middle age APP/PS1 Het mice.…”
Section: Discussionsupporting
confidence: 93%
“…Whereas the VSE of APP/PS1 Het mice maintained fairly stable neurogenic capabilities, senescent wild type animals showed a significant reduction in proliferative and stem cells (PCNA + and Sox2 + VSE cells) (Figure 2) which may explain the reduction of mature OMP + neurons, sustentacular Sox2 + cells and VSE volume (Figure 1 and Supplementary Figure 1). Our findings are consistent with two previous studies directly exploring the effects of natural aging in the VSE (Brann and Firestein, 2010;Mechin et al, 2021), which reported an overall thinning of the vomeronasal sensory epithelium (Mechin et al, 2021) and reduced VSE neurogenesis in 2-year-old animals (Brann and Firestein, 2010). Here, we expand this current knowledge by providing novel information on the properties of the VSE in a commonly used animal model of AD (APP/PS1 Het ), revealing an unexpected preservation of the organ and its proliferative capabilities in middle age APP/PS1 Het mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1). Our findings are consistent with two previous studies (Brann andFirestein, 2010, Mechin et al, 2021), which reported an overall thinning of the vomeronasal sensory epithelium (Mechin et al, 2021) and reduced VSE neurogenesis in the marginal zone of 2-year-old animals (Brann and Firestein, 2010). Here, we provide novel information from a commonly used AD animal model (APP/PS1 Het ), revealing an unexpected preservation of the VSE proliferative capabilities in middle age APP/PS1 Het mice.…”
Section: Discussionsupporting
confidence: 93%
“…In mice, the VNO cells were shown as the Pseudorabies virus infection after experimental intranasal inoculation [14]. More recently, always in mice, the degenerative changes induced by the ageing process were characterized [15]. Finally, the relationship between vomeronasalitis and intraspecific aggressive disorders in domestic cats has been described [16], and it is the only report that links VNO spontaneous alterations to animal behavioural changes.…”
Section: Introductionmentioning
confidence: 99%